Role of the Big Data Analytic framework in Business Intelligence and its Impact: Need and Benefits - et. al., Farhad Khoshbakht, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Big Data is mixed with huge, autonomous sources like decentralized and distributed control system. For organizations that use the conventional data processing mechanism to handle and archive these large data sets, these capabilities pose an extreme obstacle. A new model has to be defined and the existing framework must be re-evaluated for the analysis and management of big data. The word Business Intelligence (BI) applies to applications, technology and activities for commercial knowledge gathering, review, incorporation and presentation. Business Intelligence’s primary aim is to facilitate quicker and stronger business decision-making process.” Therefore, the strategic review of the literature must study the trend of Information System (IS) adoption factors as a well-designed strategic diagnostic tool that can be used for essential decision-making systems to enable more effective and reliable action plans. We started with discussing some frameworks required for strategic excellence by examining the potential approaches of Big Data Analytics (BDA) and Business Intelligence (BI). In the end, we would design an integrated application that functions as an organization's strategic performance management diagnostic tool. “In general, the emphasis and reach are on the corporate decision-making mechanism, there are some specifics on the analysis, but every conceivable tool and instrument is not specified, the concept is sufficiently concrete to assist in the creation of steps. This research paper therefore examines the position of the system for big data analytics and market intelligence.